印尼零基础学习者汉语声调教学：五度与三度教学法效果对比及策略探究 - 王神黎, Julianti; Hao, Zhang (Bambuti | Fakultas Bahasa dan Budaya Universitas Darma Persada, 2025)
Abstract With the rise of the global “Chinese fever”, tone instruction has become increasingly important in International Chinese Language Education but remains a major challenge due to its complexity. Learners from different regions and linguistic backgrounds exhibit systematic errors in tone acquisition, particularly beginner Indonesian learners. This study, based on Interlanguage Theory, Contrastive Analysis Theory and Experimental Phonetics, focuses on the acquisition of monosyllabic Chinese tones by Indonesian beginners. A total of 84 learners were divided into two groups (A and B), receiving instruction through the Five-Degree and Three-Degree Teaching Methods. Using perceptual discrimination and acoustic analysis, data were analyzed with Praat software to compare the effectiveness of both methods. Results show that while the Three-Degree Teaching Method is more effective, overall mastery remains suboptimal. T4 (falling tone, 去声调) is the easiest, while T2 (rising tone, 阳平调) is the most challenging. Based on these findings, the study analyzes error sources and proposes strategies: optimizing the teaching sequence (T4 → T3 → half-T3 → T1 → T2), strengthening tone awareness, emphasizing systematic mastery, and integrating AI-assisted instruction. These findings provide practical insights for improving Chinese tone instruction for Indonesian learners. 摘要 随着全球“汉语热”升温，汉语声调教学在国际中文教育教学中的重要性日益凸显，但因其复杂性成为教学难题。不同地区和语言背景的学习者在声调习得上存在规律性错误，尤其是印尼零基础学习者。本研究以中介语理论、对比分析理论和实验语音学为支撑，聚焦印尼零基础学习者的汉语单字调学习。通过选取84名学习者并分为A、B两组，分别采用五度教学法和三度教学法开展教学。研究运用听辨实验法和声学实验法，借助语音软件Praat分析数据，对比两种教学法的效果。研究发现，三度教学法在提升学习者声调掌握程度上效果更佳，但整体效果仍未达理想状态。去声调最易被学习者辨认和产出，阳平调则最难。基于此，文章深入剖析了偏误产生的原因，涵盖汉语声调特征、学习者自身因素以及教师教学因素。同时，针对性地提出教学建议，如结合两种教学法并优化教学顺序、强化声调特征学习、注重声调系统整体把握以及利用人工智能辅助教学，以此提高教学有效性，为印尼汉语声调教学提供有益参考。